Determinan Faktor Komitmen Organisasi di Lingkungan Persatuan Istri Prajurit Batalyon Infanteri 141 Muara Enim - Maharani, RR Afenty (Journal of Business & Applied Management, 2024)
In an organization, commitment is a very important thing because it can be used as a measure of general performance success as shown by the ethics of members in complying with organizational rules. This research departs from the ethical problems of members of the Chandra Kirana Soldier's Wife (Persit) in carrying out organizational commitment. The population and in this research is the entire population as a sampling technique by paying attention to organizational commitment variables (age, tenure, level of education, communication, leadership, organizational culture and Organizational Climate). The data used is primary data in the form of respondents' answers regarding research variables obtained through distributing questionnaires. To test the relationship between research variables, multiple regression analysis techniques were used using SPSS version 20 software. The research results showed that: Age has no effect on organizational commitment among members of Persit Kartika Chandra Kirana Infantry Battalion 141, tenure of office has a positive effect on organizational commitment, education level has a positive effect on organizational commitment, communication has a positive effect on organizational commitment, leadership has a positive effect on organizational commitment, organizational culture has a positive effect on organizational commitment, work climate has a positive effect on organizational commitment